New Method for Solving Systems of Two-Dimensional Non-linear Volterra Integro-Differential Equations - Mostafa Eslami (Science Faculty of Chiang Mai University, 2019)
In this paper two methods, Homotopy Perturbation Method (HPM) and a new modified Homotopy Perturbation Method (NHPM) for the solution of non-linear systems of two-dimensional Volterra integro-differential equations are compared. Comparison between the solutions and the exact solution shows that the NHPM is more effective and accurate for solving systems of two-dimensional Volterra integro-differential equations